The impact of bases of auditing quality, which relating of external auditor’s characteristics on narrow the expectation gap in auditing environment on Libya - احمد محمد الروياتي, عوض; ثابت محمد حسين, عديلة (Dirasat in Economics and Business, 2026)
This study aims to determine the effect of bases of Auditing quality that related of Libyan external Auditor characteristics on narrow Expectation Gap ,which is observing among external auditor and financial information users in Libyan business environment .Deductive –Inductive method was followed in preparing and implementing the study ,questionnaire was designed and used for collecting the data and information necessary of the study , questionnaires were distributed to358 participants (a random sample of study population), represents in external auditors and financial information users (Credit management officers in commercial Banks; staff members on universities ) in east region in Libya, some of questionnaires were distributed electronically , and some of them directly, hand by hand ,we receive 266 questionnaires suitable for analyzing in response rate 74% , researchers were used SPSS package to analysis data, the multiple regression was used for hypothesis test After study and analysis the data descript fully and test the hypothesis, the study concluded that; the Libyan external Auditor has adequate qualification, skills, independence, and he also concerned of industrial specialization, which are the bases for auditing quality, so, it has statistically effect in narrow expectation gap in Auditing profession in Libya. Rely on the results of the study the researchers recommend to concern for studying and analyzing causes of expectation gap in Auditing profession in Libya, since it is a hard problem against Auditing profession, and it will affect the confidence of Accounting information users toward a profession, in addition to, it is necessary to concern for the bases of Auditing quality, which related to Libyan external Auditor characteristics which are helping to minimize Expectation Gap.